2018
DOI: 10.4269/ajtmh.17-0903
|View full text |Cite
|
Sign up to set email alerts
|

Social Influence on Handwashing with Soap: Results from a Cluster Randomized Controlled Trial in Bangladesh

Abstract: We analyzed data from a cluster-randomized controlled trial conducted among 20 schools in Rajshahi, Bangladesh, to explore the role of social influence on handwashing with soap (HWWS) in a primary school setting. Using data collected through covert video cameras outside of school latrines, we used robust Poisson regression analysis to assess the impact of social influence-defined as the presence of another person near the handwashing location-on HWWS after a toileting event. In adjusted analyses, we found a 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
0
12
0
1
Order By: Relevance
“…The salience of the nurture motive in our study population is consistent with other studies of students handwashing. For example, a study in Bangladesh that used covert video cameras to record handwashing behaviour found numerous instances of older children helping younger children washing hands and modelling positive behaviours for one another 29. Students in our study responded positively to the nurture messages, suggesting that positive peer pressures are a potential avenue for improving HWWS in schools.…”
Section: Discussionmentioning
confidence: 60%
“…The salience of the nurture motive in our study population is consistent with other studies of students handwashing. For example, a study in Bangladesh that used covert video cameras to record handwashing behaviour found numerous instances of older children helping younger children washing hands and modelling positive behaviours for one another 29. Students in our study responded positively to the nurture messages, suggesting that positive peer pressures are a potential avenue for improving HWWS in schools.…”
Section: Discussionmentioning
confidence: 60%
“…Can social influence or peer effects improve hand‐washing engagement? Recent works have identified that social influence plays an important role in many behaviors like exercise or diet (Aral & Nicolaides, ; Lim & Meer, ), and there is some initial evidence that it can play a role in individual hygiene (Grover et al., ). There is certainly a need for rigorous and carefully designed field experiments on a large population scale, to identify and measure the causal effect of digital nudges, incentives, and peer influence on public hand‐washing engagement of air travelers as well as the mechanisms of health‐enhancing human behavior change.…”
Section: Discussionmentioning
confidence: 99%
“…Can social influence or peer effects improve smart hand-washing engagement? Recent works have identified that social influence plays an important role in many behaviors like exercise or diet 51,52 , and there is some initial evidence that it can play a role on individual hygiene 53 . There is certainly a need for rigorous and carefully designed field experiments on large population scale to identify and measure the causal effect of digital nudges, incentives and peer influence on public hand washing engagement of air travelers as well as the mechanisms of health-enhancing human behavior change.…”
Section: Discussionmentioning
confidence: 99%